The prospects of narrow reading in Arabic language for religious students (Islamic Studies) - Al-Muslim Mustapa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Arabic is an important asset for students in Islamic studies to master knowledge related to Islamic studies. One of the techniques in Arabic Extensive Reading is Narrow Reading. NR Techniques are suitable for Arabic language studies for the purpose of studying Islamic knowledge as it is deemed to be focused and guided. Initially, in-depth analysis has been conducted on reading habits in Islamic studies and its compatibility with NR philosophy. NR Techniques are found to have the prospects of achieving success in Arabic language learning for Islamic studies. The basis for the use of NR techniques is the relevant reading material in terms of ideas, lexical and semantic. The same association was found in the text and references written in the science of Islamic studies. This is reinforced by linguistic analysis of two texts from different works of Islamic Jurisprudence. The results of the analysis show the relationship between the two texts in terms of lexical and semantic. The use of Narrow Reading techniques will help students to reduce the burden of understanding and also lead to efficiency and effectiveness in the reading of Arabic text.